Analisis Efektifitas UU Nomor 16 Tahun 2019 Terhadap Pencegahan Pernikahan Usia Dini - Ipetu, Ainun S; Thalib, Mutia Cherawaty; Abdussamad, Zamroni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Early marriage is a marriage involving one or both parties under the age of 18. This study aims to analyze the effectiveness of Law Number 16 of 2019 on the Prevention of Early Marriage. This research is a type of normative juridical research, namely research that is focused on examining the application of rules or norms in positive law. Law Number 16 of 2019 concerning the Second Amendment to Law Number 1 of 1974 concerning Marriage has the main objective of preventing early marriage in Indonesia. Conclusions about the effectiveness of this law on preventing early marriage may vary, depending on various factors such as implementation, law enforcement, and socio-cultural factors that influence the policy.